Democracia e esportes em Atenas - Lessa, Fábio de Souza (2008)
In the commonsense among specialists there was a democratization in sports practice in the Classical Athens (centuries V and IV B.C.). That said, we suggest to study the relation between democracy and the dissemination of athletic practices in the Athenian polis, using athletic ´Çü gures from Greek vases as a form to explain this fact, such as the discobulos, which is considered as a symbol of the Athenian democracy.
Há um consenso entre os especialistas que na Atenas Clássica (séculos V e IV a.C.) houve uma democratização das práticas esportivas. Partindo desta a´Çü rmação, propomos estudar a relação entre a democracia e a disseminação das práticas atléticas na pólis dos atenienses, a partir da representação nos vasos gregos da modalidade esportiva do lançamento de disco. Tal escolha se explica pelo discóbolo ter sido o ícone da democracia ateniense.
Keywords: Classical Athens; Democracy; Sports practice; Greek vases; Atenas Clássica^lpt; Democracia; Práticas esportivas; Vasos gregos; Civilizaciones antiguas; Siglos V-IV a.d.C; Vida social; Deporte